Multidose methotrexate treatment of cornual pregnancy after in vitro fertilization: Two case reports - T. Loukopoulos; A. Zikopoulos; E. Mastora; A. Galani; S. Stavros; E. Kolibianakis (Elsevier, 2022)
Background: An ectopic pregnancy, when the gestational sac is implanted outside of the uterine cavity, can be life-threatening. A cornual pregnancy is the most dangerous type of ectopic pregnancy since it can be misdiagnosed easily and has high mortality rate. It is diagnosed when the implantation site is at the junction between the fallopian tube and the uterus. For a successful outcome, early diagnosis and management are critical. The traditional management is surgical, involving cornual resection or hysterectomy, which, however, affects fertility. Thus, conservative management involving administration of methotrexate should always be considered. Case presentation: The article describes to two women in their early forties with no previous children (G1, P0) and diagnosed with a cornual pregnancy at 7 and 8 weeks of gestation following in vitro fertilization. Given their hemodynamic stability and their desire to conserve fertility they were treated conservatively. The two patients had similar ultrasound findings and blood results. The main difference was the presence of an embryonic heart beat in one case. Successful management was accomplished with multidose methotrexate and leucovorin during hospitalization for 8 days and close monitoring for the next 30 days as outpatients. In addition, the second woman was given a transvaginal injection of potassium chloride (KCL) to stop embryonic cardiac activity. Conclusion: Conservative management of cornual pregnancies applying multidose therapy of methotrexate and leucovorin is a safe treatment when patients are asymptomatic and preserves fertility.